Structural and Morphological Properties of Nanostructured ZnO Particles Grown by Ultrasonic Spray Pyrolysis Method with Horizontal Furnace - G. Flores-Carrasco; J. Carrillo-López; J. A. Luna-López; R. Martínez-Martínez; N. D. Espinosa-Torres; M. E. Rabanal (Advances in Materials Science and Engineering)
ZnO nanoparticles were synthesized in a horizontal furnace at 500°C using different zinc nitrate hexahydrate concentrations (0.01 and 0.1 M) as reactive solution by ultrasonic spray pyrolysis method. The physical-chemical properties of synthesized ZnO nanoparticles have been characterized by thermogravimetric analysis (TGA), X-ray diffraction (XRD), scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS), and high resolution transmission electron microscopy (HRTEM). With the TGA is has optimized the temperature at which the initial reactive (Zn(NO3)2·6H2O), is decomposed completely to give way to its corresponding oxide, ZnO. SEM revealed secondary particles with a quasispherical shape that do not change significantly with the increasing of precursor solution concentration as well as some content of the broken spheres. Increasing the precursor solution concentration leads to the increase in the average size of ZnO secondary particles from 248±73 to 470±160 nm; XRD reveals the similar tendency for the crystallite size which changes from 23±4 to 45±4 nm. HRTEM implies that the secondary particles are with hierarchical structure composed of primary nanosized subunits. These results showed that the precursor concentration plays an important role in the evolution on the size, stoichiometry, and morphology of ZnO nanoparticles.